Gastrointestinal bleeding - Gralnek, Ian M. (Endoscopy, 2014)
A number of interesting abstracts on gastrointestinal bleeding and endoscopy were presented at Digestive Disease Week (DDW) this year (3 – 6 May 2014, Chicago, Illinois). The following abstracts are those that have particular high clinical importance and the potential for direct impact on the endoscopic care of patients with gastrointestinal bleeding.